A comparative study of different amine-based solvents for CO2-capture using the rate-based approach. (10th January 2017) - Hüser, Nicole; Schmitz, Oliver; Kenig, Eugeny Y.
Abstract: The amine-based solvent 2-amino-2-methylpropanol (AMP) represents a promising potential absorbent for efficient CO2 -capture. In this work, a numerical study of AMP in absorption/desorption loops at industrial scale was carried out. To evaluate the AMP performance, it was compared to the state-of-the-art solvent monoethanolamine (MEA). Sensitivity studies were performed to identify performance-limiting and performance-enhancing factors. Subsequent optimisation revealed that replacement of MEA by AMP can reduce the energy requirements of CO2 -capture units by 20% and the solvent consumption by 15%. Highlights: We studied CO2 absorption performance of the solvent AMP at industrial scale. Energy requirements of CO2 -capture units can be reduced by 20% compared to MEA. Solvent consumption of CO2 -capture units can be reduced by 15% compared to MEA. Model-based identification of optimal solvents with reduced number of experiments.